Efforts to Support Small Business and Private Entrepreneurship by the State in Uzbekistan - Gaybullaev Rakhim Murodovich (International Journal on Economics, Finance and Sustainable Development, 2022)
The article explains that small business and private entrepreneurship are an important component of the economy, which has a positive effect on its effective functioning, and that the development of small business largely depends on the state's support for this sector. It is shown that the process of supporting small business and private entrepreneurship in Uzbekistan, their legal protection, and the effective use of world experience and its positive aspects in this regard are the most urgent tasks today, when structural changes are being implemented in the economy.